MODERASI GENDER PADA HUBUNGAN ANTARA ORGANIZATONAL CITIZENSHIP BEHAVIOUR DENGAN WORK- FAMILY CONFLICT, ROLE OVERLOAD, DAN JOB SETRESS - Widjajani, Susi; Kurniati, Yuli (Jurnal Analisis Bisnis Ekonomi, 2010)
The purpose of this research is to examine the relationship between Organizational Citizenship Behaviour (OCB) leaadership and Work-Family Conflict (WFC), Role Overload, Job Setress, with gender as a moderating variable. Variables in this research were measured via a survey of 132 couples employee and have child in the Yogyakarta. Hierarchical Regression Analysis were used to examine the effect of OCB on WFC, Role Overload, and Job Setress. Results showed that higher levels of OCB are associated with levels of emplyee role overload, job setress, and WFC. The findings also suggest that the relationship between OCB and WFC is moderated by gender, such that the relationship is stronger among woman than among man. Finally, the results have an important implication to managers in designing job.